Frontal Brain Asymmetry in Depression With Comorbid Anxiety: A Neuropsychological Investigation. - Nelson, Brady D.; Sarapas, Casey; Robison-Andrew, E. Jenna; Altman, Sarah E.; Campbell, Miranda L.; Shankman, Stewart A. (Journal of Abnormal Psychology, 2012)
The approach-withdrawal model posits that depression and anxiety are associated with a relative right asymmetry in frontal brain activity. Most studies have tested this model using measures of cortical brain activity such as electroencephalography. However, neuropsychological tasks that differentially use left versus right frontal cortical regions can also be used to test hypotheses from the model. In two independent samples (Study 1 and 2), the present study investigated the performance of currently depressed individuals with or without a comorbid anxiety disorder and healthy controls on neuropsy-chological tasks tapping primarily left (verbal fluency) or right (design fluency) frontal brain regions. Across both samples, results indicated that comorbid participants performed more poorly than depressed only and control participants on design fluency, while all groups showed equivalent performance on verbal fluency. Moreover, comorbid participants showed "asymmetrical" performance on these two tasks (i.e., poorer design [right frontal] relative to verbal [left frontal] fluency), whereas depressed only and control participants showed approximately symmetrical profiles of performance. Results from these two samples suggest an abnormal frontal asymmetry in neurocognitive performance driven primarily by right frontal dysfunction among anxious-depressed individuals and highlight the importance of considering comorbid anxiety when examining frontal brain functioning in depression.